Optimization of sulfurization time and temperature for fabrication of Cu2ZnSnS4 (CZTS) thin films. (February 2019) - Olgar, M.A.
Abstract: In this study, growth of CZTS thin films was performed by sputter deposition of metallic precursor layers followed annealing process at different sulfurization temperatures and times. In the first stage of the study, effect of the reaction temperature for 1 s sulfurization time was investigated. XRD pattern of the sample sulfurized at 560 °C showed purer XRD pattern and better crystalline quality. Zn and Sn loss was observed for reacted samples at 540 and 580 °C. SEM images of CZTS560-1 samples revealed purer and molten-like surface structure. Optical band gap values were found 1.45 eV that are not influenced by sulfurization temperature. In the second stage, effect of the sulfurization time for sulfurization temperature at 560 °C was examined with addition of electrical characterization to the previous characterization methods. EDX results demonstrated that Zn-loss took place at higher dwell time of reaction (300 s). XRD data showed that increasing the sulfurization time above 1 s enhances the crystalline quality and contributes to form much purer CZTS structure. Raman spectroscopy confirmed presence of CZTS phase. Optical band gap values (1.45–1.48 eV) and electrical properties of the CZTS thin films were strongly influenced by [Cu]/[Sn] atomic ratio and presence of CuS based secondary phase. Highlights: CZTS thin films were grown on soda lime glass by a two-stage process. Sulfurization temperature (540, 560, and 580 °C) and time (1, 60, 300 s) were varied. Sulfurization at 560 °C presented purer and better crystalline structure. The reacted sample at 560 °C for 60 s exhibited the most promising results.